Physicochemical and cell biological characterization of PMMA bone cements modified with additives to increase bioactivity1. Issue 4 (20th December 2012) - Wolf‐Brandstetter, Cornelia; Roessler, Sophie; Storch, Sandra; Hempel, Ute; Gbureck, Uwe; Nies, Berthold; Bierbaum, Susanne; Scharnweber, Dieter
Abstract: Polymethylmethacrylate (PMMA) bone cement is the most widely used material in surgery to fix joint replacements in the bone. In this study, we propose a new approach to generate bioactive PMMA surfaces directly at the site of implantation by adding the amphiphilic molecule phosphorylated 2‐hydroxyethylmethacrylate (HEMA‐P) to commercial PMMA bone cement, both with or without addition of 1–5% soluble calcium and carbonate salts. The setting behavior as well as the mechanical properties, the bonding quality at the metal/cement interface, mineral deposition, and cellular response for different cement modifications were investigated in vitro . The addition of HEMA‐P resulted in entirely positive effects with respect to proliferation and differentiation of osteoblast‐like cells (SaOs‐2) and a very tight contact at the metal/cement interface. No detrimental changes of other properties were detected. The additional incorporation of salts provoked an increased deposition of calcium phosphate minerals but no further improvement in SaOs‐2 cell differentiation. A significant decrease in polarization resistance for cements with high salt content (5%) was attributed to debonding between metal and cement. The results suggest an improved clinical performance of PMMA/HEMA‐P composites, which might be further enhanced by small amounts of the soluble salts. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2013.